Accuracy and reliability of a videogrammetry system in the analysis of displacement of Wistar rats - Silva Junior, Osvaldo Tadeu Da; Santiago, Paulo Roberto; Curiacos, Jose Alexandre Almeida Leme; Santos, Julio Wilson Dos (Universidade Estadual Paulista, 2017)
AbstractAims The behavior of laboratory animals has been studied through displacement, with different objectives by researchers.Methods Although different methods have already been used in the tracking of laboratory animals, manual tracking mode videogrammetry for 2D analysis of displacement has not been observed in animal studies. The aim of this study was to verify the accuracy and reliability of determining the displacement of Wistar rats by means of videogrammetry software Dvideo. The accuracy (between the known distance and distance traced) was determined by 3 different evaluators twice consecutive, by videoing a course of 10 meters in the enriched environment together with further analysis of the displacement of the midpoint marked on an apparatus. To calculate reliability (accuracy of the measurement system) and reproducibility (precision of the evaluators) to obtain the ratio of precision to tolerance (P/T), eight animals were filmed for 10 minutes in the enriched environment and analysis of distance covered by one of the animals by three different reviewers thrice consecutive.Results The results obtained in the course of 10 meters of the known distance demonstrated accuracy of 0.10 m, precision of 0.05 m, and bias of 0.07 m. In the reliability test during the 10 minutes of displacement (m) of animal, the ratio of precision to tolerance (P/T) = 0.1 m was found between three different evaluators, demonstrating adequate capacity of the measure.Conclusion The manual tracking mode of the Dvideo presented high reliability and it can be employed for the displacement analysis of studies with rat experimental models.
Keywords: displacement; videogrammetry; 2D analysis